2022
DOI: 10.1186/s12916-022-02663-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting COVID-19 vaccine effectiveness identified from 290 cross-country observational studies until February 2022: a meta-analysis and meta-regression

Abstract: Background Observational studies made it possible to assess the impact of risk factors on the long-term effectiveness of mRNA and adenoviral vector (AdV) vaccines against COVID-19. Methods A computerized literature search was undertaken using the MEDLINE, EMBASE, and MedRxiv databases to identify eligible studies, with no language restrictions, published up to 28 February 2022. Eligible were observational studies assessing vaccine effectiveness (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…As vaccine protection diminishes over time, receiving an early vaccination reduces the risk of early infection but may increase the risk of later infection. This has been noted in several studies [ 9 , 10 , 11 ].…”
Section: Introductionsupporting
confidence: 70%
“…As vaccine protection diminishes over time, receiving an early vaccination reduces the risk of early infection but may increase the risk of later infection. This has been noted in several studies [ 9 , 10 , 11 ].…”
Section: Introductionsupporting
confidence: 70%
“…Multiple factors may contribute to the fact that vaccination does not protect against critical COVID-19, including age, vaccine type, virus variant, and immunosuppression. 26 In addition, other, unknown, factors may contribute to the lack of vaccine efficacy in vaccinated patients presenting with severe COVID-19. Despite these findings, in the absence of a statistically significant difference, it is important to note that the proportions of patients with severe complications, NIV failure, and in-hospital mortality were higher in unvaccinated patients than in those who had received at least one dose of vaccine in the propensity-matched sample.…”
Section: Discussionmentioning
confidence: 99%
“…pacientes não vacinados a pacientes que receberam pelo menos uma dose de vacina, mostrou um melhor prognóstico em pacientes com vacinação completa ou incompleta. Múltiplos fatores podem contribuir para o fato de a vacinação não proteger contra a COVID-19 crítica, incluindo a idade, o tipo de vacina, a variante do vírus e a imunossupressão (26). Além disso, outros fatores desconhecidos podem contribuir para a falta de eficácia da vacina em pacientes vacinados com COVID-19 grave.…”
unclassified
“…Proportion of individuals producing neutralizing humoral immunity after vaccination was lower among people with obesity compared to those without [47] . A meta-analysis of observational studies reported that presence of one or more comorbidities (including obesity, diabetes, hypertension) was associated with lower protection against COVID-19 and severe COVID-19 [48] . Immunogenicity of vaccines appear to be lower in people with diabetes irrespective of the type of vaccine and weaker with higher BMI and worse glucose control [49] .…”
Section: Preventing and Managing Covid-19 In People With Metabolic Sy...mentioning
confidence: 99%